Diari perjuangan : pembelaan isteri terhadap penahanan tidak sah suami di bawah ISA - Aliza Jaafar, 1958- (Sg. Buloh, Selangor Darul Ehsan : Focus Approach, 2002)
Author's account of her struggling to free her husband against detention without legal trial under the Malaysian Internal Security Act.
In Malay.
Koleksi Sumbangan : Dr. Syed Husin Ali.
Keywords: Saari Sungib, -- 1957-; Political prisoners -- Malaysia; Malaysia -- Politics and government; Internal security -- Malaysia